Proclaim liberty throughout all the land : a history of church and state in America - Gaustad, Edwin S. (Edwin Scott) (Religion in American life., 2003)
Should prayer be allowed in public schools? Should biology be taught according to Darwin or to the book of Genesis? Why is polygamy against the law? These are just a few of the questions that touch our lives directly and emerge out of the separation of church and state. In this volume, one of the most distinguished scholars of American religious history traces the complicated relationship of church and state from the early colonial period, through the unique American experiment in religious liberty after the Revolution, to the ongoing debate over religious issues in our schools and communities. Edwin Gaustad relates entertaining and edifying accounts of headline-grabbing court trials involving polygamy, witchcraft, and church taxation. He quotes moving passages from the speeches and writings of American Presidents and Supreme Court justices to prove that, to paraphrase Michelangelo, "religious liberty is made up of a series of trifles, but religious liberty is no trifle."